CAUSALITY: POVERTY, INCOME INEQUALITY, AND ECONOMICS GROWTH - Rohani Rohani; Ikhsan Amar Jusman (Sekolah Tinggi Pariwisata Mataram, 2021)
The research objective is to explain the causality of poverty, income inequality, and economic growth in the Bantaeng district. The data analysis used is descriptive analysis and inductive analysis. The method used is the Granger Causality. The data used is panel data with a period of 2015-2019 with 8 districts. The data source comes from the BPS report. The results showed that (1) there was no causality between poverty and income inequality (2) There is no causality between poverty and economic growth (3) There is a causality between income inequality and economic growth